Can We Use the Fellow Eye Biometric Data to Predict IOL Power?. (4th May 2017) - De Bernardo, Maddalena; Zeppa, Lucio; Forte, Raimondo; Cennamo, Michela; Caliendo, Luisa; Zeppa, Lucia; Rosa, Nicola
ABSTRACT: Purpose : To study the correlation between right (RE) and left eye (LE) keratometry readings (K) and axial lengths (AL) in a population-based sample of normal subjects. Methods : In a cross-sectional retrospective study conducted at S. Giuseppe Moscati Hospital, Avellino, Italy, 4516 eyes of 2258 patients with a mean age of 67 ± 16.36 years (range 18–96 years) were included. Partial coherence interferometry data obtained in right (RE) and left (LE) eyes were analyzed and correlated. Results : The average K was 44.01 ± 1.50 diopters (D) (range 39.09–49.89 D) in the RE and 44.04 ± 1.53 D (range 39.63–51.89 D) in the LE (p = 0.0075). 4.5% of the patients (101) presented with differences in the corneal power ≥ 1 D, corresponding to a difference of roughly 1 D in the IOL power. The average AL was 23.89 ± 1.77 mm (range 19.09–35.15 mm) in the RE and 23.84 ± 1.68 mm (range 19.23–35.04 mm) in the LE (p = 0.0018). 19.2% of the patients (433) presented with differences in the AL ≥ 0.4 mm, corresponding to a difference of roughly 1 D in the IOL power. Conclusions : In calculating the IOL power, we must be aware of these results when we measure the fellow eye to validate the measurements in the first eye. In the case of postcataract refractive error, the outcome could be used for the second eye only when symmetric biometric findings are present.